The Farming Land Tenure by Corporation: People’s Economic Rights Protection Perspective - Multifiah, Multifiah; Ekawaty, Marlina; Herdiastiti, Debby Radina (Institute of Research and Community Service, University of Brawijaya, 2015)
Recruitment is a series of events to find and attract job applicants motivation, ability, skills and knowledge required in order to cover the flaws identified in the staffing plan. In most of the industrial age, family networks continue to complement the main base manpower recruitment. The purpose of this study is to determine the role of social capital networks as a method of recruitment. The analysis method used is descriptive qualitative approach.